(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Sábato Magaldi, a Brazilian theater critic from Minas Gerais, played many roles in the theater, contributing extensively to the study, criticism and formation of theater. This article discusses the work of processing, inventorying and researching the Sábato Magaldi Collection, held by the UFMG Collection of Writers from Minas Gerais, and aims to discuss its processes and methodological bases. It aims to present some of the results obtained during the process of preparing, describing and inventorying his collection, as well as pointing out some reflections on the impact of this collection on theatrical historiography. To this end, it discusses the definition of a personal collection and the need for contextual practice when describing the archive.